Employer demand ontology - Forbes, David; Wongthongtham, Pornpit; Terblanche, C.; Pakdeetrakulwong, U. (2018)
While in the previous two chapters the area of healthcare is focused, in this chapter and the next chapter workforce management area is emphasised. We firstly present development of Employer Demand Ontology (EDO) in this chapter.